Open Source Certification and Educational Process - Khoroshilov, Alexey (Electronic Communications of the EASST, 2009)
This paper discusses possibilities to benefit software engineering and computer sciences educational process from involving students in open source software certification activities. On the other hand the open source certification community can take advantages of this involvement if it cooperates with educational one. The situation is considered in the context of Russian higher institutes of education but the conclusions can be applicable to other institutes as well.